Above-ground energy reserves and annual accumulation of energy in shrub and herb layers in ass. Quercus frainetto+Quercus cerris - Festuca heterophylla+Poa nemoralis in the Vakarel mountains - Ljubenova, Mariana (Macedonian Journal of Ecology and Environment, 1994)
The above ground phytomass energy reserves of the shrub layer ammounts to 3,1S4 • 10 6 KJ • ha"1 with an increase of 1,63-106 KJ -ha"1 down the slope, 71,46% of them being concentrated in the seedling phytomass. The herb layer reserves are 15,342 • 10 6 KJ • ha"1 (down the slope they increase with o,38 • 106 KJ•ha"1); the contribution of grass species being 71,46 %, of mixo-herbosa -20,31 %, of sedges - 4,21 %, of legumes species - 4,09 %. The annual accumulation of energy in shrub and herb layers are 34,95 % and 73,46% of their reserves.